(3GdCZGfjs - (3Ydj Hf GdMSjf Hf eMeO Hf CMeO Hf GdgjKe GdeQhGfj GdCehj GdbQTj, CHh GdaQL GdCUHgGfj, J (B356 (3g` s
(3ChdgG (B:s
(3Chd GdehLhO bhdg (B: (3bGd eDda gPG GdcJGH hdYd HYV jJUaM Pdc jfcQ s
(3BNQgG (B:s
(3bGd NGdO Hf Lejd MOKi QLGd eQI Hfi YGeQ Cf RhL djdi hCHGgG NQLG ai CeQ WQb GdMi Edi ecI aCQSdJ HCeI dgG Edi GdeLfhf aOYJg aCbGe s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B277 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B78 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B336s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd s
(3GdfSNI HgG CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs